Peran Guru PAI dalam Membantu Siswa Bermasalah di Sekolah - Daksa Nizam Adila; Fikri Ariq Sofyan; Akmalul Jamil; Erba Rozalina Yuliyanti (Fakultas Pendidikan Islam dan Keguruan Universitas Garut, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in assisting students with problems at school, including the types of roles they play, the approaches they use, collaboration with guidance and counseling (BK) teachers, and the impact of coaching on student behavioral changes. This study uses a qualitative approach with descriptive methods, with data collection techniques through observation, interviews, and documentation of Islamic Religious Education (PAI) teachers, guidance and counseling teachers, and students with problems. The results show that Islamic Religious Education (PAI) teachers play an important role not only as educators, but also as moral guides, role models, and character builders through preventive, curative, and educational roles. The humanistic, persuasive, and religious approach used by Islamic Religious Education (PAI) teachers has proven effective in helping students recognize mistakes and improve their behavior. In addition, collaboration between Islamic Religious Education (PAI) teachers and guidance and counseling teachers is a supporting factor in comprehensively handling problem students. The impact of the role of Islamic Religious Education (PAI) teachers is seen in changes in student behavior towards a more positive direction, such as increased discipline, politeness, responsibility, and learning motivation, as well as the creation of a religious climate and a character-based school culture. Keywords: Role of Islamic Religious Education Teachers, problem students, character building, Islamic religious education